Deforestation and Transboundary Haze in Indonesia: Path Dependence and Elite Influences. (September 2014) - Atkinson, Christopher L.
Indonesia is the world's third-largest emitter of greenhouse gases, primarily due to its timber and forest activities. Timber-related fires are common in Indonesian peat forests, resulting in a noxious haze that has been the cause of periodic economic and public health crises. In this article, the phenomenon of transboundary haze is examined in the light of path dependence, historical institutionalism and elite theory. An evaluation of Indonesia's policy process with environmental legislation and enforcement, prospects for future policy development and discussion of the inability of Indonesia to deal effectively with haze and other environmental problems are addressed in the light of theory. The article concludes that the haze problem has historically been a microcosm of what is wrong with environmental policy in Indonesia, and that new incentive programmes like Reducing Emissions from Deforestation and Forest Degradation (REDD+) aside, no significant change from the historical path may be reasonably expected unless Indonesia can seek to end or at least reduce the influence of crony relationships on regulatory structures and administration, and implement an independent programme of its own with appropriate oversight and resources for addressing environmental degradation and enforcement of regulations. 印尼是世界上第三大温室气体排放国，主要是来源于其木材和森林方面的活动。木材相关的火灾在印尼泥炭林中十分常见，这导致了有害雾霾始终是周期性经济和公共健康危机的原因。在本文中，通过路径依赖、历史制度主义和精英理论研究了跨境雾霾现象。本文从理论上探讨了印尼环境立法和执法的评价，未来政策发展的展望，并认为印尼没有能力有效应对雾霾和其他环境问题。本文的结论是，雾霾问题历来是印尼的环境政策出现问题的一个缩影，除了像REDD+（通过减少森林砍伐、遏制森林退化来降低排放）这样的新激励计划以外，从历史路径中没有显著的变化可以进行合理预测，除非印尼可以结束或者至少降低裙带关系对监管体系和管理的影响，并且形成一个独立的程序，通过适当的监督和方法解决环境退化和规定实施的问题。